Evaluating the performance of the cylindrical Shell for deffernt mathematical Equation of the trangential fiber (Damascus University Journal for engineering sciences, 2021)
Shell structurals are a very great importance buildings,due to their architecural beauty and its potential to cover large areas without columns .Particularly cylindrical shell which frequently used in industrial buildings for multiple uses.Different behavior of cylindrical shells according to the mathematical equation governing the tangential fiber .In this research it was be given a different mathematical equations , such as giving the equation of circle,or cut equivalent, ellipse, and other equations for the tangetial fiber, and then have a study of the transformation of the internal forces in the shell ,then it was developed a computer programme paticular to calculate the internal forces in cylindrical shell , and organized the results hn four tables.In this research it was to determine the best ratio between the span and the height of the cylindrical shell, and determine the best curve can be used in Cylindrical  shell.
Keywords: Shell; height of the shell; span of the shell; cylindrical-intrnal force; tangential forces